If f(x) is a polynomial function which satisfy the relation (f(x))2 f"(x)=(f"(x))3 f'(x), f'(0)=f'(1)=f'(-1)=0,f(0)=4, f(±1)=3, then f"(i) (where i=√7) is equal to

Please show complete solution

3 years ago


Answers : (1)

f'(0) = f'(-1) = f'(1) = 0
\Rightarrow f'(x) = ax(x-1)(x+1), a = constant
\int df(x) = \int ax(x-1)(x+1)dx
f(x) = a(\frac{x^{4}}{4}-\frac{x^{2}}{2}) + c, c = constant
f(0) = a(\frac{0^{4}}{4}-\frac{0^{2}}{2}) + c = 4
\Rightarrow c = 4
f(\pm 1) = a(\frac{(\pm 1)^{4}}{4}-\frac{(\pm 1)^{2}}{2}) + 4 = 3
\frac{-a}{4} = -1
a = 4
f(x) = x^{4}-2x^{2}+4
f'(x) = 4x^{3}-4x
f''(x) = 12x^{2}-4
f''(\sqrt{7}) = 12(\sqrt{7})^{2}-4 = 80
Thanks & Regards
Jitender Singh
IIT Delhi
askIITians Faculty
6 months ago

Post Your Answer

More Questions On Differential Calculus

Ask Experts

Have any Question? Ask Experts
Post Question
Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
if |sinx+ cosx|=|sinx|+|cosx| then x belongs to which quadrant
the answer should be 1 Quadrant or 3 quadrant. Coz It will be true only when both of them will be positive or both will be negative.
Aditya Wahi 6 months ago
Find integral solution to the eqation [x][y]=x+y. show that all non-integral solution lie on exactly two lines. determine these lines. Thanks
[x]=x- frac(x)= x-x’ [y]=y-frac(y) =y-y\ [x][y]=(x- frac(x))(y-frac(y) ) xy- xy’- x’y-x’y’ = x+y xy- xy’- x’y-x’y’ – x- y is...
Sher Mohammad 6 months ago
help ...please explain fully
oh sorry i couldnot chat yesterday. i logged off. i will explain. you can do this question in many ways easiest method to save time is differentiate both sides of the equation. keeping...
esha singh 6 months ago
its a bit lengthy (limits method) i find this method more appealing.
esha singh 6 months ago
is the answer none of these ?
esha singh 6 months ago
circles of radii 5,5,8 touch each other externally. Find the radius of the circle which touches all the three circles internally.
Pushkar Aditya 18 days ago
if you draw yhe diagram, and put C1,C2 the centre of circle with r=5. c3 the centre of circle of r=3. Since circle(c3) touch the both circle C 3 C 1 =C 3 C 1 -->C3 lies on perp. bisector of...
Abhishek Singh 16 days ago
@ abhishek singh ..that is the easy one . it is for externally that u r telling .. the question reads internally my frnd.
sarim khan 17 days ago
how can we find the value of sin22degree or all such angles?
If you mean sin 22.5 degree, then we can find it using sin half angle formula. sin 22 degree can not be found using this method. One way to find approximate value of sin 22 degree is to...
Satyajit Samal 3 months ago
please give me more explanation for expansion of sin22 degree
vaishali chandel 3 months ago
please give me more explanation for expansion of sin22 degree
vaishali chandel 3 months ago
IF A+B+C = 180, THEN (SIN 2A – SIN 2B – SIN 2C) /(SIN 2B – SIN 2A – SIN 2C) =
Hello student, Please find the answer to your question below Sin 2A - Sin 2B – Sin 2C = 4 Cos A Sin B sin C SIN 2B – SIN 2A – SIN 2C = 4 sinA Sin B cos C Now you can divide...
Nishant Vora 4 months ago
View all Questions »